ENVIRONMENTAL ASPECTS OF SUSTAINABLE TOURISM DEVELOPMENT - Todorov, Predrag; Mihailović, Branko; Brzaković, Pavle (The Business of Tourism, 2023)
Abstract: Rapid development of eco-tourism is reflected in an almost equally rapid growth in the number of researchers who draw attention to potentially detrimental and destructive consequences of tourism growth. Sustainable tourism and eco-tourism destinations are crucially important for sustainable development, which has emerged as a logical need to stop the accelerated economic growth based on unlimited exploitation of available resources. Tourism and the environment are intrinsically linked and interdependent, thus eco-management of a tourist destination is crucial for future development and sustainability. Nowadays tourists motivation to visit a destination is increasingly governed by the principles of sustainability, therefore decision-makers and local communities should pay more attention to the laws and rules connected with the protection of the environment as well as efficient implementation of the regulations. This paper aims to provide a better insight into the eco-management system which is in the service of the development of tourist destinations and their sustainability by offering a comprehensive overview of the literature which includes revolutionary research as well as papers published in up-to-date magazines. The concept of eco-tourism destination management requires finding new strategies as well as revising various management strategies in order to ensure the conservation of biodiversity.